Discomfort associated with fixed orthodontic appliances: determinant factors and influence on quality of life - Leandro Silva Marques; Saul Martins Paiva; Raquel Gonçalves Vieira-Andrade; Luciano José Pereira; Maria Letícia Ramos-Jorge (Dental Press Editora, 2014)
OBJECTIVE: To investigate the determinant factors of discomfort attributed to the use of fixed orthodontic appliance and the effect on the quality of life of adolescents. MATERIAL AND METHODS : Two hundred and seventy-two individuals aged between 9 and 18 years old, enrolled in public and private schools and undergoing orthodontic treatment with fixed appliance participated in this cross-sectional study. The participants were randomly selected from a sample comprising 62,496 individuals of the same age group. Data was collected by means of questionnaires and an interview. Discomfort intensity and bio-psychosocial variables were assessed using the Oral Impact on Daily Performance questionnaire. Self-esteem was determined using the Global Negative Self-Evaluation questionnaire. Statistical analysis involved the chi-square test and both simple and multiple Poisson regression analyses. RESULTS: Although most individuals did not present discomfort, there was a prevalence of 15.9% of impact on individuals' daily life exclusively due to the use of fixed orthodontic appliance . Age [PR: 3.2 (95% CI: 1.2-8.5)], speech impairment [PR: 2.2 (95% CI: 1.1-4.6)], poor oral hygiene [PR: 2.4 (95% CI: 1.2-4.8)] and tooth mobility [PR: 3.9 (95% CI: 1.8-8.1)] remained independently associated with a greater prevalence of discomfort (P ≤ 0.05). CONCLUSIONS: Discomfort associated with the use of fixed orthodontic appliances exerted a negative influence on the quality of life of the adolescents comprising the present study. The determinants of this association were age, poor oral hygiene, speech impairment and tooth mobility.